Surveying a rich new Vista. - Clack, Keith (Bookseller, 2007)
This article presents an overview of the business and computing book sector leading with the boost in titles following the launch of Microsoft Vista. Recommendation is made to follow customer feedback as to which books best augment the new program. Business books have no parallel event but subjects such as trade in India and China, reissues of classic titles by Peter Drucker, and a popular history of the shipping container "The Box" have kept sales moving.